Pulmonary vein stenosis in ex-preterm infants – a challenging but important diagnosis for neonatalogists. (7th June 2011) - Mitchell, J; Heuchan, A; Knight, B; Mcleod, K; Powls, A
Abstract : Objective: To raise awareness of pulmonary vein stenosis (PVS) to neonatologists. Background: PVS is rare, affecting approximately 2 per 100 000 children under the age of 2 years. Recent evidence suggests many children with PVS were premature and/or have cardiac lesions, particularly patent ductus arteriosus (PDA), atrial septal defects (ASD) and ventricular septal defects (VSD). PVS is difficult to diagnosis and can be mislabelled as chronic lung disease (CLD). Doppler echocardiography can diagnose this condition. Untreated PVS is frequently progressive with less than 50% survival at 5 years. Prognosis may be improved if diagnosed early and when treated with newer surgical techniques. Method: Two cases are used to illustrate these issues. An 18-month old infant born at 27 weeks gestation that had a VSD closed in infancy presented with breathlessness and failure to thrive. She was treated for gastro-oesophageal reflux and respiratory infection before being found to have three obstructed pulmonary veins. She improved following sutureless repair of her veins but long-term prognosis is guarded due to restenosis. A 5 month old infant born at 28 weeks gestation with history of a PDA who has since been diagnosed with oxygen-dependant CLD was coincidentally found to have stenosis of one pulmonary vein during echocardiography. A month later two pulmonary veins were stenosed. His is stable but progression is likely and he may require surgery. Conclusion: Review of literature raises the question: Should we be more vigorous in looking for PVS in babies whose clinical findings are suggestive of CLD?